Advances in alternative splicing identification: deep learning and pantranscriptome - Shen, Fei; Hu, Chenyang; Huang, Xin; He, Hao; Yang, Deng; Zhao, Jirong; Yang, Xiaozeng (Frontiers in Plant Science, 2023)
In plants, alternative splicing is a crucial mechanism for regulating gene expression at the posttranscriptional level, which leads to diverse proteins by generating multiple mature mRNA isoforms and diversify the gene regulation. Due to the complexity and variability of this process, accurate identification of splicing events is a vital step in studying alternative splicing. This article presents the application of alternative splicing algorithms with or without reference genomes in plants, as well as the integration of advanced deep learning techniques for improved detection accuracy. In addition, we also discuss alternative splicing studies in the pan-genomic background and the usefulness of integrated strategies for fully profiling alternative splicing.